THE ROLE OF SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP IN ENSURING THE ECONOMIC SECURITY OF THE COUNTRY - Yormatov Ilmidin Toshmatovich (Scholar Express Journals, 2022)
The sustainable development of small business and private entrepreneurship, which is considered an important driver of the republic's economy, is closely related to its economic security. In this regard, the artful article provides a comprehensive analysis of the issues of economic security of small business and private entrepreneurship. Scientific studies, opinions and positions of foreign and domestic scientists on this issue are studied in detail, a comparison is made of the differences between them and general views. As a result, the authors have developed conclusions and recommendations
Keywords: Economic security, small business, systematic analysis, business entities, security threat, extortion